Behavioral effects of polylactic acid microplastics on the tadpoles of Pelophylax nigromaculatus - Li, Zihan; Chen, Youhua (Ecotoxicology and environmental safety, 2024)
Polylactic acid microplastics (PLA-MPs), biobased plastics made from renewable resources, are considered to be a potential solution for alleviating the pollution pressure of plastics; however, the potential environmental risks of PLA-MPs must be further evaluated. In this study, the effects of PLA-MPs on the tadpoles of Pelophylax nigromaculatus were investigated by designing different PLA-MP exposure experiments. We found that PLA-MPs negatively affected the survival, growth and development of tadpoles. In addition, in open field tests, PLA-MPs also reduced tadpole locomotion while resulting in more repetitive searching behavior within a restricted area. This effect was more pronounced at higher concentrations of PLA-MPs (20 mg/mL) and in combination with the heavy metal Cd2+. In the tank tests, PLA-MPs increased tadpole aggregation, and their combined effect with Cd2+ resulted in a tendency for tadpole aggregation to increase and then decrease, with the distribution tending to favor aggregation in edge regions. PLA-MPs also strongly inhibited the spatiotemporal exploratory activities of tadpoles in the tanks. This study provides a more detailed investigation of the behavioral effects of PLA-MPs on tadpoles and provides a theoretical basis for subsequent ecotoxicological studies of PLA-MPs. •Polylactic acid microplastics negatively affect growth and motility in tadpoles.•Polylactic acid microplastics increase anxiety levels in tadpoles, increase the probability of intensive search behavior.•Polylactic acid microplastics increase aggregation of tadpole populations and tend to be marginally distributed.